Performance Assessment of Municipal Solid Waste Management Model of Lahore: A Case Study of Two Turkish Contractors: Assessment of Solid Waste Management Model in Lahore - Haydar, Sajjad; Afaq, Misbah; Hussain, Ghulam; Ahmad, Ghayas (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2016)
The solid waste management (SWM) trends are changing rapidly in big urban centers. For improving efficiency of service delivery,invariably the collection and transportation services are outsourced to private contractors. The Lahore Waste Management Company (LWMC) also outsourced their services to two Turkish contractors: Contractor-A and Contractor-B. The objective of this study was to evaluate the performance of these contractors. For this purpose two (02) performance assessment models were developed;one for service recipients and second for SWM contractor’s staff. Key performance indicators (KPIs), as developed by the LWMC, were evaluated and the relevant indicators concerning techno-social aspects were selected corresponding to each model, to assess the service delivery level by the contractors. A questionnaire was developed for each model. Data was collected from 40 Union Councils (UCs) of Lahore. 384 service beneficiaries and 68 concerned officials were interviewed from all the selected UCs. The Statistical Package for Social Sciences (SPSS) was used for data analysis. The analysis revealed that from the service beneficiary point of view, the service delivery is satisfactory, however requires certain improvements. It is also deduced that overall performance of both the SWM contractors is encouraging; however, they need improvements primarily in some sectors, like public awareness plans, staff trainings and availability of vehicles and equipment. Overall, performance of Contractor-B is better in all KPIs as compared to the Contractor-A.